Evolution trend and weakening mechanism of mode-I fracture characteristics of granite under coupled thermo-hydro-mechanical and thermal treatments. (November 2022) - Zhang, Dengke; Meng, Tao; Taherdangkoo, Reza; Feng, Gan; Wen, Liu; Butscher, Christoph
Highlights: The evolution law of fracture toughness of granite after coupled THM and thermal treatment was compared. The FPZ length evolution law of granite at different loading stages after coupled THM and thermal treatment was obtained. The microscopic damage degree of granite after coupled THM and thermal treatment was compared. Abstract: Understanding the fracture behavior and fracture-morphology evolution of granite after coupled thermo-hydro-mechanical (THM) environment is important for many geotechnical projects. Previous studies mostly focused on the fracture-response mechanism of rocks after a thermal treatment, whereas only a few studies were conducted on the fracture toughness, fracture-process-zone (FPZ) size, and fracture-morphology evolution of granite after the THM multifield coupling. Therefore, a coupled THM damage treatment (i.e., THM-induced damage) of granite was carried out using a self-developed, high-temperature, and high-pressure multifield coupling triaxial universal tester. Subsequently, a series of test methods was employed, which included the full-field 3D digital-image correlation technique (real-time tracking of the strain/displacement field on the specimen surface), X-ray computed tomography scanning technique (to obtain the microdamage structure inside the specimen), and 3D laser scanner (to obtain the section morphology of the specimen). These methods were employed to study the response mechanism of mode-I fracture of a granite specimen (fracture toughness, fracture trajectory, FPZ size, and fractal dimension of the section topography). Furthermore, to elucidate the correlation between the coupled THM induced damage and fracture characteristics of granite, the same experimental test was also carried out on the granite using a thermal treatment. The result show that the evolution pattern of the fracture and morphological parameters of granite after the coupled THM treatment was different from that using only the thermal treatment, and the value of these physical parameters fluctuated at approximately 400 °C–500 °C. This is due to the limitation of the triaxial stress on the thermal expansion (25 °C–300 °C), competitive effect of "opening" and "closing" of micropores/microcracks (400 °C–500 °C), and deterioration of the coupled THM field (600 °C–650 °C). The results provide insights and theoretical guidance for high-temperature underground rock-mass engineering such as deep nuclear-waste reservoir.